2013
DOI: 10.1111/een.12073
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of oviposition time and enhanced larval feeding: two potential benefits of aggregative oviposition for the viburnum leaf beetle

Abstract: 1. Although aggregation in non-social arthropods is common, its adaptive value is not always clear. Oviposition behaviour of the viburnum leaf beetle (Pyrrhalta viburni ) is aggregative, with females preferring to lay eggs on twigs already infested by conspecifics. We previously showed that aggregative oviposition aided in overcoming host plant defences. Here we explore two additional benefits of this behaviour: reduction of time investment in oviposition; and improvement of host use by larval group feeding.2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The insect oviposition mode can have a significant impact on egg survival and larval performance. When eggs are laid in clusters, neonate larvae often show gregarious feeding behavior, which benefits offspring performance in some insect species (Denno and Benrey 1997;Clark and Faeth 1998;Fordyce 2003;Allen 2010;Desurmont et al 2014;Martínez et al 2017). On the other hand, many herbivorous insects lay single eggs, spreading them over a larger area, possibly as a means of reducing predation risk and competition (Root and Kareiva 1984;Nufio and Papaj 2001).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The insect oviposition mode can have a significant impact on egg survival and larval performance. When eggs are laid in clusters, neonate larvae often show gregarious feeding behavior, which benefits offspring performance in some insect species (Denno and Benrey 1997;Clark and Faeth 1998;Fordyce 2003;Allen 2010;Desurmont et al 2014;Martínez et al 2017). On the other hand, many herbivorous insects lay single eggs, spreading them over a larger area, possibly as a means of reducing predation risk and competition (Root and Kareiva 1984;Nufio and Papaj 2001).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…One complicating factor that our study does not address is the recently reported observation that P. viburni benefits from larval group feeding [ 28 ]. Although P. viburni larvae do not feed gregariously in the strict sense [ 29 ], they do tend to form loose groups feeding on the undersides of young Viburnum leaves, a behavior that is facilitated by the fact that egg masses from adult P. viburni are often laid in clusters along infested twigs [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although P. viburni larvae do not feed gregariously in the strict sense [ 29 ], they do tend to form loose groups feeding on the undersides of young Viburnum leaves, a behavior that is facilitated by the fact that egg masses from adult P. viburni are often laid in clusters along infested twigs [ 30 ]. Larval density was shown to be positively correlated with pupation success and, under certain conditions, adult weight on a range of Viburnum hosts [ 28 ]. Thus, larval density may play a role in the success of host-switching in P. viburni and, conversely, results of the choice-tests could have been different if larvae had been tested individually.…”
Section: Resultsmentioning
confidence: 99%
“…It is not surprising, then, that ovipositing herbivorous insects show a diversity of responses to conspecifics that affect group size, ranging from aversion through neutrality to conspecific attraction. Conspecifics can enhance oviposition, either directly by their presence or indirectly, by their modification of plant quality (Judd & Borden 1992, Navasero & Ramaswamy 1993, Prokopy & Reynolds 1998, Raitanen et al 2014, Desurmont et al 2014, Durisko et al 2014. However, by far the most frequently reported effect is that insects tend to avoid host plants that bear conspecific eggs or larvae (Rothschild & Schoonhoven 1977, Williams & Gilbert 1981, Shapiro 1981, Roitberg & Prokopy 1987, Pettersson 1992, Kumari et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Prokopy and Reynolds (1998) and Papaj et al (1992) suggested that adult female Mediterranean fruit flies cue in to the presence of other conspecific adults as an indicator of host plant quality, using "public information" (Danchin et al 2004) in a manner analogous to the phenomenon of "mate copying" in which females increase their preference for individual males after observing them being accepted by other females. Herbivorous insects may benefit from large group size by enhancement of antipredator defence (Lawrence 1990, Hunter 2000, Riipi et al 2001, by being better able to overcome host defences (Clark & Faeth 1997, Campbell & Stastny 2014, Desurmont et al 2014 or by constructing better protection against harsh climate (Kuussaari et al 2004, Kuussaari & Singer 2017.…”
Section: Discussionmentioning
confidence: 99%